Technology Entrepreneurship Project (ENT 600) : Decathlon / Muhamad Zulfazli Amir - Amir, Muhamad Zulfazli (2021)
Nowadays. choosing the capital City of Malaysia as the initial hub of our business, we are targeting to introduce our product in this busy city before expand the business to the whole region of Malaysia. Our aim is to serve the best technology smart watch in Malaysia which can help people in their life. Smart watch also want to introduce the label as the most customer-friendly company which concerned on the quality of the products produced. When it comes to fitness industry activities, the first things that we need to bear in mind is about health, wellness, sports, safety and apparel. One of the ways maintaining about the health and safety when conducting the activities is by wearing good outfit such as tight sportswear and smart watch. The benefits and trendy of the smart watch makes the brands exist and live on market. Smart watch from Decathlon is one of the products which has been successfully marketed and promoted. There are some advantages that can allow consumer attraction. Smart watch is appropriate for everyone, and particularly for the athletes. This product is ergonomic and can be used by all. While they have many advantages, there are few drawbacks that cause the customer problems once they buy and eventually wear the smart watch. The main issue that the company always face is about the material that being used. Poor quality of the rubber bands sometimes makes customers feel disappointed. Other than that, this smart watch being produce with no choices of design and colours. Design and colours are too lame and bored. This can cause the customers turn to the others brand. Not all people in this world love the same colours and design. That's why we need the variety of colours and design. Customers always give sizing grievances. We do need to manufacture the smart watch with more sizes and meet customer needs because all people enjoy working out nowadays. To conclude, we need to come up with a better smart watch version that can solve the problems as above in order to satisfy the customers' needs.